Genetic Variation for Epidermal Conductance in Peanut. Issue 2 (1st March 2014) - Rosas‐Anderson, Pablo; Sinclair, Thomas R.; Balota, Maria; Tallury, Shyam; Isleib, Thomas G.; Rufty, Thomas
ABSTRACT: Peanut ( Arachis hypogaea L.) is an important legume that is often grown in drought‐prone areas. Low epidermal conductance (EC) may delay the dehydration of leaves and improve plant survival of severe water‐deficit stress. No reports of genetic variation for EC in peanut have been found in the literature. Therefore, the main objective of this study was to document genetic variation for EC among 21 peanut ( Arachis spp.) genotypes in two greenhouse experiments and a field experiment. The effects of water‐deficit stress on EC and the association between EC and stomata density (SD) were also investigated. Tests for an influence of water‐deficit stress on EC were inconclusive. Comparison of EC and SD among genotypes failed to show any significant correlations in the various test environments. However, genetic variation for EC in peanut was found in both greenhouse experiments, with genotypes TMV 2, PI 298639, and VA 98R having very low EC. In the field, genotype SPT 06‐07 was found to have low EC. These results indicate that selection of genotypes with low EC is a viable approach in identifying peanut genotypes with improved capacity to survive severe soil water deficits.